Infusion or Decoction Extracts ofHelianthus annuusLeaves: Potential Inhibitors for QS system and Biofilm Formation in Pseudomonas aeruginosa - SESAL, NÜZHET CENK (My University, 2020)
Pseudomonas aeruginosais one of the drug-resistant opportunistic pathogenswith the ability to form biofilm and to produce a number of virulence factors via Quorum Sensing (QS) regulation. Most researchers have focused on QS inhibition to overcome the drug resistance problem.QS inhibitormolecules are investigated from natural resources.In the present study, anti-QS activities of ethyl acetate extracts of decoction and infusion samples from Helianthus annuusleaveswere tested on biosensor strains of P.aeruginosa(lasB-gfp, rhlA-gfp andpqsA-gfp), as well as anti-biofilm activities on PAO1wild type. H.annuusleaf sampleswere firstly infused or decocted and then extracted with ethyl acetate. Theefficacies ofinfusion or decoction extracts were examinedat the concentrationsof 240, 120,and60μg/mlin 96-well microplatesand evaluated in Citation 3 multimode microplate reader (Biotek). The inhibition rates of decoction extracts were recorded as 70.61% for las, 44.09% for rhland 83.77% for pqssystem at 240 μg/ml. The biofilm inhibition percentages of the extracts were determined to be 50.82% (±1.36). Moreover, inhibition rates for infusion extracts were detected as 62.08% for las, 45.15% for rhland 77.79% for pqs, and 53.88% (±3.94) for biofilm formation. In conclusion, the potential efficacies of the extracts of decocted or infused H.annuusleaves were demonstratedon QS system and biofilmformation of P.aeruginosa. However, there is a need for more detailed investigations and determination of the active substances that have QSI and anti-biofilm effect.

Pseudomonas aeruginosa, Quorum Sensing (QS) regülasyonu yoluyla biyofilm oluşturma ve bir dizi virülans faktörüüretme kabiliyetine sahip ilaca dirençli fırsatçı patojenlerden biridir. Çoğu araştırmacı, ilaç direnci sorunlarının üstesinden gelmek için QS inhibisyonuna odaklanmıştır. QS inhibitör molekülleri doğal kaynaklardan araştırılmaktadır. Bu çalışmada, Helianthus annuus yapraklarından elde edilen dekoksiyonve infüzyon örneklerininetil asetat özütlerinin anti-QS aktiviteleri, P. aeruginosa'nın biyosensör suşları (lasB-gfp, rhlA-gfp vepqsA-gfp) üzerinde ve ayrıca anti-biyofilm aktiviteleri PAO1 yabanıl tipindetest edilmiştir. H. annuusyaprak örnekleri önce infüze veya dekokteedildi ve daha sonra bunların etil asetat ile özütüçıkarıldı. İnfüzyon veya dekoksiyon özütlerinin etkisi96 kuyucuklumikroplakalarda 240, 120 ve 60 μg/ml konsantrasyonlarında incelendi ve Citation 3 multimodmikroplaka okuyucuda (Biotek) değerlendirildi.Dekoksiyonözütlerinin inhibisyon oranları, 240 μg/ml’delasiçin%70.61, rhliçin %44.09 ve pqs sistemiiçin%83.77 olarak kaydedildi. Özütlerinbiyofilm inhibisyon yüzdelerininise %50.82 (± 1.36) olduğu belirlenmiştir. Ayrıca infüzyon özütleriiçin inhibisyon oranları lasiçin% 62.08, rhliçin% 45.15 ve pqsiçin% 77.79 ve biyofilm oluşumu için%53.88 (± 3.94) olarak tespit edildi. Sonuç olarak, infüzeveya dekokteedilmiş H.annuusyapraközütlerininpotansiyel etkileri P. aeruginosa'nın QS sistemi ve biyofilm oluşumu üzerinde gösterilmiştir. Bununla birlikte, QSI ve anti-biyofilm etkiye sahip aktif maddelerin daha ayrıntılıaraştırmalarına ve belirlenmesine ihtiyaç vardır.
Helianthus annuus Yapraklarının İnfüzyon veya Dekoksiyon Özütleri: Pseudomonas aeruginosa’nın QS Sistemi ve Biyofilm Oluşumu Üzerine Potansiyel İnhibitörler